Bridging the gap: Multi-sector perspectives on human, domestic animal, and wildlife leptospirosis in Ontario, Canada - Kellie C. Libera; E. Jane Parmley; Katie M. Clow; Lauren E. Grant; J. Scott Weese; Claire M. Jardine (PLoS ONE, 2026)
Although leptospirosis is one of the most common zoonotic diseases worldwide, limited surveillance and poor coordination between human and animal health sectors have resulted in scarce and disparate data on its occurrence. Strengthening integrated surveillance requires cross-sector collaboration, beginning with the engagement of key organizations. The aims of this study were to 1) determine key health experts’ awareness and risk perceptions of leptospirosis and of zoonotic disease surveillance in Ontario, Canada, and 2) examine key components of engagement, such as perceived value and interest, during the initial stages of developing an integrated leptospirosis surveillance framework. A web-based survey was sent to 543 experts in human, animal, and environmental health in Ontario, and analyzed using a mixed-methods approach to identify key factors influencing perceptions of leptospirosis, including views on Leptospira distribution, the impact of human behavior, and the influence of environmental conditions. Leptospirosis was recognized as a health threat in Ontario by 90% (74/82) of respondents, and 91% (70/77) indicated that current surveillance efforts are inadequate. A higher proportion of animal health sector respondents identified leptospirosis as a threat to human (93%, 37/40) and animal health (90%, 44/49) compared to public health sector respondents (76%, 25/33 and 83%, 25/30, respectively). All participants (81/81) acknowledged the benefits of integrated surveillance over the current siloed approach. Our findings highlight that key public and animal health experts perceive leptospirosis as a health threat in Ontario and support more integrated disease surveillance to better respond to this emerging zoonotic pathogen.